Stiletto network : inside the women's power circles that are changing the face of business - Ryckman, Pamela (AMACOM, American Management Association, 2013)
Formidable ladies across professions are convening at unprecedented rates, forming salons, dinner groups, and networking circles--and collaborating to achieve clout and success. A new girls' network is alive and set to hyperdrive. "Stiletto Network" is about those groups.